Aligning the Disarrayed: Snapshot and Aquatint in Visualizing Memory - Astika Pramesti (NIM:17014005), Anastasia
The forming of human’s personality cannot be separated from their smallest group’s influences, such as the family. The transfer of values and the socializing process that is being done constantly can stimulate someone’s implicit memory, in their subconscious. The implicit memory is used for remembering without thinking and also can facilitate the performance of activities we perform. The author feels that implicit memory also influences her interest in certain visual, technical and media patterns in her work. The author's interest in a particular visual pattern is then recorded into snapshot photographs of pieces of objects and landscapes in the environment around her and processed into a form of printmaking work made using intaglio aquatint technique. The long series of printmaking work processes are also felt to be able to translate the essence of implicit memory that is recorded unconsciously by the writer, in which the author enjoys a long, sequential, and structured process in working. Through this work the author tries to visualize the elements of memory or implicit memory that are recorded unconsciously while interpreting what factors influence the formation of implicit memory. Then it can be concluded that implicit memory, as for the author is not present in visualization of events, but more than that, through the adaptation of forms of her surroundings, such as; lines, composition, shapes, scopes, patterns, as well as the long process of aquatint.